2015
DOI: 10.1007/s12035-015-9617-0
|View full text |Cite
|
Sign up to set email alerts
|

Indoleamine-2,3-Dioxygenase/Kynurenine Pathway as a Potential Pharmacological Target to Treat Depression Associated with Diabetes

Abstract: Diabetes is a chronic disease associated with depression whose pathophysiological mechanisms that associate these conditions are not fully elucidated. However, the activation of the indoleamine-2,3-dioxygenase (IDO), an enzyme that participate of the tryptophan metabolism leading to a decrease of serotonin (5-HT) levels and whose expression is associated with an immune system activation, has been proposed as a common mechanism that links depression and diabetes. To test this hypothesis, diabetic (DBT) and norm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 71 publications
(35 citation statements)
references
References 81 publications
0
34
0
1
Order By: Relevance
“…This was associated from three weeks onwards with an increased number of spinal microglia [43] and depressive-like behaviour [44]. A recent study suggested that acute minocycline treatment might ameliorate depression-like behaviour in diabetic animals [45]. However, this study did not assess whether the minocycline-induced acute antidepressant-like effect was associated with attenuation of pain hypersensitivity.…”
Section: Introductionmentioning
confidence: 83%
See 1 more Smart Citation
“…This was associated from three weeks onwards with an increased number of spinal microglia [43] and depressive-like behaviour [44]. A recent study suggested that acute minocycline treatment might ameliorate depression-like behaviour in diabetic animals [45]. However, this study did not assess whether the minocycline-induced acute antidepressant-like effect was associated with attenuation of pain hypersensitivity.…”
Section: Introductionmentioning
confidence: 83%
“…A recent study in fully established STZ-induced diabetes showed that one-day intraperitoneal treatment with minocycline reversed the diabetes-induced reduction in swimming in the FST and this acute antidepressive-like effect of minocycline was associated with suppression of a neuroinflammatory pathway in the hippocampus of diabetic animals [45]. The present study is in agreement with this recent finding and extend it by showing that the antidepressive-like effect of minocycline in established diabetes is maintained even when the daily minocycline treatment is prolonged at least up to three weeks.…”
Section: Minocycline In the Control Of Diabetes-associated Emotional mentioning
confidence: 98%
“…Beyond cytokines themselves, antidepressant-like effects have been recently reported in obese mice after pharmacological blockade of cyclooxygenase-2, an enzyme activated by cytokines . On the other hand, the opportunity of blocking other enzymatic targets of cytokines, in particular, those involved in the kynurenine pathway whose activity increases with adiposity (Favennec et al, 2015) and correlates with depressive symptoms in both obese individuals and animals, likely represents another interesting therapeutic approach, as recently suggested from findings in diabetic rats (da Silva Dias et al, 2015). Alternatively, targeting the neopterin pathway, in particular, BH4, which is a critical cofactor for monoamine synthesis and is altered in obesity (Finkelstein et al, 1982;Ledochowski et al, 1999;Oxenkrug et al, 2011;Oxenkrug, 2010), may also provide a useful way to reduce adiposity-driven inflammation and related depressive symptoms.…”
Section: Pharmacological Strategiesmentioning
confidence: 99%
“…Future studies should also include clinically depressed individuals, who might have more alterations in KP-related phenotypes, and include more prodromal markers, such as fatigue which may predict psychopathological distress (Dabaghzadeh et al 2013). Third, although imbalance in KYN metabolism is implicated in the development of psychopathological symptoms in HIV individuals (Davies et al 2010; Baran et al 2012; Cassol et al 2015), it can be found in multiple disorders including stroke (Bensimon et al 2014), diabetes (da Silva Dias et al 2015), cardiovascular disorders (Nikkheslat et al 2015), Alzheimer’s Disease (Leonard 2007), Huntington’s Disease (Mazarei and Leavitt 2015), and cancer (Hufner et al 2015). Therefore, our results regarding how KMO and KATII might influence KYN metabolism and the psychopathological distress might not be specific to HIV infection.…”
Section: Discussionmentioning
confidence: 99%